The Differences in the Influence of Fundamental Analysis on Stock Returns Between Mining Sector and Consumer Goods Sector - Mediaty, Mediaty; Habbe, Hamid; Sibulo, Rury Novita (Formosa Journal of Applied Sciences, 2023)
This study explores variations in the fundamental factors impacting stock returns by focusing on two sectors: the mining sector and the consumer goods sector. The financial metrics analyzed include Price Earning Ratio (PER), Return on Assets (ROA), and Earning Per Share (EPS). The sample comprises the financial reports from 2018 to 2022 for 12 companies, evenly split between 6 mining sector companies and 6 consumer goods sector companies listed on the LQ45 of the Indonesian Stock Exchange. The findings reveal dissimilar effects of financial analysis on stock returns in the mining and consumer goods sectors. In the mining sector, the combined influence of PER, ROA, and EPS is positive but insignificant on stock returns. Conversely, in the consumer goods sector, PER exhibits a positive and significant impact, ROA shows a negative and insignificant effect, and EPS has a positive yet insignificant effect.